15-hydroxy-6α, 12-epoxy-7β, 10αH, 11βH-spiroax-4-ene-12-one sensitizes rectal tumor cells to anti-PD1 treatment through agonism of CD11b. (15th July 2020) - Zhao, Qingye; Lu, Lin; Du, Guowei; Wang, Zhihai; Li, Xutong; Ju, Fang
Abstract: Purpose: Although immunotherapies have resulted in durable clinical responses, not all tumor types have seen substantial benefit. Extensive recruitment and accumulation of immunosuppressive myeloid cells into the tumor tissues has been postulated as a major mechanism of resistance to immunotherapies. Strategies targeting on single immunosuppressive cell type, in combination with checkpoint inhibitors, have resulted in promising outcomes in animal studies. However, compensatory actions by untargeted cells may limit the therapeutic efficacy. CD11b is highly expressed on the myeloid cell surface with an important role in their trafficking and cellular functions.In this study, we demonstrated that activation of CD11b with 15-hydroxy-6α, 12-epoxy-7β, 10αH, 11βH-spiroax-4-ene-12-one (HESEO) enhanced the therapeutic efficacy of anti-PD1 treatment in the tumor model. Materials and methods: A syngeneic rectal tumor model was established. Different types of cells from the peripheral blood and tumor tissues were analyzed by flow cytometry. Real-time PCR was used to detect the gene expression. Therapeutic effects of HESEO combining with anti-PD1 antibody were assessed by the tumor model. Results: Our data demonstrated that HESEO repolarized tumor-associated macrophages and reduced the number of tumor-infiltrating immunosuppressive myeloid cells. We further demonstrated that HESEO and immunotherapy combination promoted tumor growth control in a syngeneic tumor model. Conclusions: Our results showed that HESEO improved anti-tumor T cell immunity and rendered anti-PD1 treatment effective in unresponsive tumor models, providing proof of concept for a new combination strategy involving molecular agonism of CD11b to bypass the limitations of current clinical strategies to overcome resistance to immunotherapies.